Hubungan Pengetahuan dan Lingkungan Dengan Perilaku Pencegahan Chikungunya pada Masyarakat Rw 01 Kelurahan Kranji Kota Bekasi - Herlina Herlina; Siti Rukayah (Jurnal Persada Husada Indonesia, 2015)
Chikungunya is a contagious disease caused by the chikungunya virus. The main symptoms are sudden fever, joint pain mainly pinned knees, toes and fingers, and spine. One of these is the prevention of disease by conducting preventive behaviour by means of the implementation of PSN, 3M Plus, and periodic larvae examination by the health officers. In 2012 and 2013 there were chikungunya outbreak in KranjiVillage with 263 cases and no deaths. This study aims to determine the relationship of knowledge and environment with chikungunya prevention behavior in community at RW 01 Kranji Village Bekasi in 2014. This study used an observational analytic cross sectional method. Total of 97 respondents were used in this study. The results showed no significant relationship between knowledge of the behavior of chikungunya prevention (OR = 0.172, P = 0.04), with the environmental behaviour of chikungunya prevention (OR = 0822, P = 0.018). Data on the chi-square test with significance level 95% (0.05). It is recommended to increase prevention activities by implementing 3M Plus, PSN and counselling to improve public knowledge related to precautionary behaviour on Chikungunya disease.